Student’ Satisfaction Toward Chemistry Learning Process At SMA Laboratorium Undiksha - Astuti, Sekar; Subagia, I Wayan; Sudiana, I Ketut (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
This research aimed to describe and explain the students’ satisfaction toward chemistry learning process and the factors influence at SMA Laboratorium Undiksha Singaraja in academic year 2016/2017. The type of this research was quantitative descriptive. The students’ grade X, XI IPA and XII IPA at SMA Laboratorium Undiksha Singaraja were used as the population of this research. Sample size was determined by Slovin formula with sampling error of 5%. Technique sampling in this research was multistage random sampling. Students interviewed were students had low and high percentage. The data were analyzed through descriptive statistics method. The results showed that the students’ satisfaction level in high category. The highest student’ satisfaction was on tangible dimension and the lowest was on empathy dimension. The satisfier factors toward chemistry learning are learning process, learning result, learning progress, teacher appreciation, and gift of the task. The dissatisfier factors toward chemistry learning are the learning atmosphere, the interaction of teacher with students, the interaction between students, and the return of task. Therefore, the teacher suggested to increase the sense of empathy and satisfier condition toward the students. Furthermore, the headmaster should be make a policy to overcome student satisfaction’ problems by paying attention to the sense of teachers’ empathy to students and the dissatisfier factors.